Effects of cadmium stress on physiological indexes and fruiting body nutritions of Agaricus brasiliensis - Lingyun Liu (Nature Portfolio, 2021)
Abstract In this study, 0, 0.5, 1, 1.5, 2, 4, 6 and 8 mg·kg−1 of cadmium were added to the cultivation materials. In order to study the effects of different concentrations of Cd stress on J1 and J77, the contents of antioxidant enzymes, proline and malondialdehyde, Cd content, agronomic traits and yield of fruiting bodies of Agaricus brasiliensis were determined, and the nutritional components such as polysaccharide, triterpene, protein, total sugar and total amino acid were determined. The results showed that the physiological indexes of strain J1 and J77 changed regularly under different concentrations of Cd stress. J1 was a high absorption and low tolerance variety, while J77 was a low absorption and high tolerance variety. Low concentration of Cd promoted the growth of strain J1, and higher concentration of Cd promoted the growth of strain J77. The contents of protein and total amino acids in the two strains changed greatly, followed by polysaccharides, which indicated that Cd stress had the greatest impact on the three nutrients, and other nutrients were not sensitive to Cd stress.